KONSEP KHILAFAH DALAM BIDANG PENDIDIKAN, POLITIK DAN HUKUM - Suhari Suhari (CV. ADIBA AISHA AMIRA, 2025)
The concept of the Caliphate, rooted in Islamic tradition, contains important principles that can be applied in the fields of modern politics and law. In a political context, the Caliph concept emphasizes leadership that is fair, transparent and accountable to society and God. This leadership is based on strong moral and ethical values, which aim to achieve prosperity and social justice. In the legal field, this concept encourages fair and equitable application of the law, as well as impartial law enforcement. The legal system based on the Caliphate concept also prioritizes the protection of human rights and individual freedoms, while maintaining the values and norms of society. The implementation of the Caliphate concept in modern politics and law can offer a holistic and balanced approach, capable of responding to contemporary challenges while still respecting traditional and religious values.